The role of genetic and epigenetic factors on the development of cognitive deficits in patients with severe trauma after repeated anesthesia (literature review) - S. N. Kuchina; I. M. Spivak; A. V. Shchegolev; A. I. Levshankov (Вестник анестезиологии и реаниматологии)
Introduction. When a severe combined injury occurs in a patient, various biochemical, humoral, cellular and pathophysiological mechanisms of protection against death occur. Immediately after receiving an injury, the patient is hospitalized in a hospital for medical care, where every effort is made to stabilize the condition, resorting to the appointment of various instrumental and laboratory tests. The development and course of traumatic illness, and treatment outcomes in patients with similar injuries are sometimes dramatically different. Based on this, it was suggested that there is a genetic basis for the regularity of the disease, as well as that exogenous factors themselves can affect certain molecular genetic markers, primarily telomere length.The objective was to summarize the current literature data on the study of changes in telomere length, as well as the influence of exogenous and endogenous factors on their shortening. To determine the prospects of studying the effect of polymorphic alleles of various genes on the development of a pathological condition in a certain cohort, namely the development of cognitive dysfunction in patients with severe trauma after repeated anesthesia.Materials and methods. The literature search and analysis was performed in the medical information systems PubMed and eLibrary, using the keywords «telomere», «trauma», «cognitive», and «anesthesia».Results. Since 1950, data on the study of human telomeres began to be published abroad. Between 2002 and the present, 39 articles were published on PubMed when searching for the keywords «anesthesia» and «telomeres»; by keywords «cognitive», «trauma», «telomeres» – 27. Most articles are devoted to the effect of childhood trauma on changes in telomere length, as well as the assessment of short telomeres in patients with various cognitive deficits. However, there are no articles devoted to studying the effect of repeated anesthesia, as an exogenous factor, on the genetic apparatus of a patient with severe combined trauma.Conclusion. The literature highlights the influence of various exogenous factors on the shortening of telomere length, especially in the context of childhood trauma, cognitive impairment in various observed groups. The section related to the effects of anesthesia and their number, the consequences for the genetic apparatus of a particular person, is open for study.